Subliminally presented and stored objects capture spatial attention. - Astle, D; Nobre, A; Scerif, G (2010)
When objects disappear from view, we can still bring them to mind, at least for brief periods of time, because we can represent those objects in visual short-term memory (VSTM) (Sperling, 1960; Cowan, 2001). A defining characteristic of this representation is that it is topographic, that is, it preserves a spatial organization based on the original visual percept (Vogel and Machizawa, 2004; Astle et al., 2009; Kuo et al., 2009). Recent research has also shown that features or locations of visual items that match those being maintained in conscious VSTM automatically capture our attention (Awh and Jonides, 2001; Olivers et al., 2006; Soto et al., 2008). But do objects leave some trace that can guide spatial attention, even without participants intentionally remembering them? Furthermore, could subliminally presented objects leave a topographically arranged representation that can capture attention? We presented objects either supraliminally or subliminally and then 1 s later re-presented one of those objects in a new location, as a "probe" shape. As participants made an arbitrary perceptual judgment on the probe shape, their covert spatial attention was drawn to the original location of that shape, regardless of whether its initial presentation had been supraliminal or subliminal. We demonstrate this with neural and behavioral measures of memory-driven attentional capture. These findings reveal the existence of a topographically arranged store of "visual" objects, the content of which is beyond our explicit awareness but which nonetheless guides spatial attention.